Association between muscular strength and mortality in clinical populations: a systematic review and meta-analysis - Jochem,C; Leitzmann,M; Volaklis,K; Aune,D; Strasser,B (Journal of the American Medical Directors Association (JAMDA): long-term care: management, applied research and clinical issues, 2019)
ObjectivesTo assess the relationship between muscular strength measures and mortality in outpatient populations with chronic diseases such as cancer, chronic obstructive pulmonary disease, renal disease, and metabolic and vascular diseases, and in critically ill hospitalized patients.DesignA systematic review and random-effects meta-analysis of prospective cohort studies was performed.Setting and participantsThe databases Medline, Embase, Clinical Trial Register, and Cochrane Trial Register were searched from inception until September 30, 2018. The systematic literature review yielded 39 studies with a total of 39,852 participants.ResultsLowest vs highest category of muscular strength revealed a statistically significant increased risk of all-cause mortality with a hazard ratio (HR) and 95% confidence intervals (CI) of 1.80 (95% CI 1.54–2.10). Lower muscular strength was associated with enhanced mortality in patients with cancer (HR 2.40; 95% CI 1.57–3.69), critical illness (HR 2.06; 95% CI 1.33–3.21), renal disease (HR 1.84; 95% CI 1.37–2.47), metabolic and vascular diseases (HR 1.64; 95% CI 1.26–2.14), and chronic obstructive pulmonary disease (HR 1.36; 95% CI 1.16–1.61). Conversely, a 5-kg higher level of muscular strength conferred a reduced risk of overall mortality (HR 0.72; 95% CI 0.59–0.89) and was accompanied by a reduction in mortality in patients with metabolic and vascular diseases (HR 0.52; 95% CI 0.29–0.91), critical illness (HR 0.78; 95% CI 0.61–0.99), and renal disease (HR 0.82; 95% CI 0.73–0.91).Conclusions and implicationsMuscular strength is inversely associated with mortality risk in various acute and chronic conditions. Future trials should focus on developing validated cut-points for diagnosing low muscular strength and their predictive value for hard end-points.